2013
DOI: 10.1016/j.bjid.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and fasting glucose impairment among HIV patients three years after the first antiretroviral regimen in a Brazilian AIDS outpatient clinic

Abstract: These data show high chance of dyslipidemia after initiation of ART. Long-term follow-up will help identify the impact of ART on cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
11
2
Order By: Relevance
“…Although increased oxidative stress [35] and dyslipidemia [9, 36] are some of the most evident side effects, in our study, no differences in glucose and total cholesterol levels were observed after therapeutic intervention. However, we cannot exclude that longer treatment could provoke these problems, as Pinto Neto et al [35] observed that dyslipidemia and glucose disturbances occurred after three years of cART use. On the other hand, in our study, patients showed a significant increase in triglyceride levels already in the first months of treatment, with no influence of the scheme used, protease inhibitors (PI), or NNRTI (data not shown).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Although increased oxidative stress [35] and dyslipidemia [9, 36] are some of the most evident side effects, in our study, no differences in glucose and total cholesterol levels were observed after therapeutic intervention. However, we cannot exclude that longer treatment could provoke these problems, as Pinto Neto et al [35] observed that dyslipidemia and glucose disturbances occurred after three years of cART use. On the other hand, in our study, patients showed a significant increase in triglyceride levels already in the first months of treatment, with no influence of the scheme used, protease inhibitors (PI), or NNRTI (data not shown).…”
Section: Discussioncontrasting
confidence: 61%
“…Despite the benefits of cART in the stabilization of HIV infection, there is evidence that the therapy is accompanied by some adverse effects, especially considering its long-term administration [9, 35]. Although increased oxidative stress [35] and dyslipidemia [9, 36] are some of the most evident side effects, in our study, no differences in glucose and total cholesterol levels were observed after therapeutic intervention.…”
Section: Discussioncontrasting
confidence: 55%
“…According to the D:A:D, a consortium assessing adverse events of anti-HIV drugs, the risk associated to certain PI’s (indinavir, lopinavir/ritonavir, abacavir) was consistently lower than the one calculated to the annual increment in risk associated to advanced age and current smoking habit [67]. The use of lopinavir/ritonavir [68], stavudine [63], efavirenz [69] and nelfinavir, zidovudine/lamivudine and didanosine/stavudine [70] have already been reported as causative of dyslipedemia by at least one of the following mechanisms (i) increased TG levels, (ii) increased LDL-c levels, and (iii) increased HDL-c levels.…”
Section: Reviewmentioning
confidence: 99%
“…Association between cART and DRCs has been long suspected [ 4 , 6 , 7 ]. Studies have provided evidence showing that this association may depend not only on the duration of exposure to cART [ 8 ] but also the type of cART regimen taken [ 4 ]. In other words, while cART is considered a providential life-saving treatment for persons living with HIV (PLWH), it also has the potential of taking away lives by exposing recipients to an array of unwanted illnesses like diabetes mellitus and related complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some experts have reported these associations only with regimens containing protease inhibitors [ 13 ], while others have described DRCs association with all types cART regimens [ 6 , 7 , 14 ]. The average time duration from cART initiation to the development of DRCs also significantly differed from one study to another [ 8 , 14 ]. However, these results are perhaps due to differences in patient characteristics.…”
Section: Introductionmentioning
confidence: 99%